BATU TABUNG BERPRASASTI DI CANDI GUNUNG SARI (JAWA TENGAH) DAN NAMA MATA ANGIN DALAM BAHASA JAWA KUNO - Baskoro Daru Tjahjono; Arlo Griffths; Veronique Degroot (Balai Arkeologi Yogyakarta, 2014)
This article presents an architectural and epigraphical study of several objects recovered from the Central Javanese temple site of Gunung Sari. The site has yielded unique cylindrical stone objects, some of which bear short inscriptions in Old Javanese language indicating the directions of space. Based on architectural arguments, we conclude that the temple was a Śaiva monument. The cylindrical objects were most likely placed originally in the floor of the platform of the temple, where they covered foundation deposits placed during the construction of the temple in connection with the ritual preparation of the ground plan. Although objects exactly identical in shape have thus far not been discovered in Java, objects that had different shapes but similar ritual functions can be identified at other more or less contemporary sites in the region. Some of these bear inscriptions. The inscriptions of Candi Gunung Sari are, however, unique in that they offer by far the oldest (nearly) complete system of eight directions of space expressed in Javanese terms.